Effects of multitask training on cognition and motor control in people with schizophrenia spectrum disorders. - Tzu-Yun Chien; Jen-Suh Chern; San-Ping Wang; Yu Yang (PLoS ONE)
Schizophrenia spectrum disorder (SSD) is a disabling mental illness that causes considerable deficits in motor and cognitive functions. The purpose of this study was to examine the effects of combining traditional multitask training (TMT) and video games--a new form of multitask training (video game multitask training VGMT)--on cognition and motor control performance in people with SSD. This was a quasi-experimental, pretest-posttest design study. A total of 25 patients participated in this study voluntarily (13 males and 12 females, average age = 59.61 years, SD- 11.46 years). All participants underwent two stages of training. The first stage involved TMT, and the second stage involved VGMT. Each training stage was 12 weeks long, with sessions twice a week that lasted for 40 minutes. Cognition, upper extremity motor and postural control performance, and functional mobility and subjective balance confidence were measured at three times: before and after the first-stage training and after the second-stage training. The results revealed that TMT and the combination of TMT and VGMT improved SSD patient's cognition, upper extremity motor control, functional mobility and postural control performance. The subjective confidence of balance during the performance of daily activities was also mildly improved. Training with multitasks in the form of video games tended to further improve the outcome measures. Patients with SSD could benefit from regular participation in various forms of multitasking activities. Whether video games training are better than TMT in improving the functional ability of people with SSD needs further investigation. Study protocol registration: Clinicaltrials.gov, ID: NCT04629898. Registered brief title: Level of Immersion of Virtual Reality and Cognition and Motor Performance in Patients of Schizophrenia Spectrum Disorder.